2016
DOI: 10.2134/jeq2015.05.0256
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Antibiotics and Antibiotic Resistance during Digestion and Composting: A Review

Abstract: Antibiotics and antibiotic-resistant bacteria (ARB) enter the environment through municipal and agricultural waste streams and pose a potential risk to human and livestock health through either direct exposure to antibiotic-resistant pathogens or selective pressure on the soil microbial community. This review summarizes current literature on the fate of antibiotics, ARB, and antibiotic resistance genes (ARGs) during anaerobic digestion and composting of manure and wastewater residuals. Studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(95 citation statements)
references
References 75 publications
(93 reference statements)
4
90
0
1
Order By: Relevance
“…Diverse removal patterns were observed for the antibiotics, ARBs and ARGs during anaerobic digestion which is in complete agreement with previously reported studies (Youngquist et al, 2016). ARGs was achieved by cyclic activated sludge system (Wen et al, 2016).…”
Section: Treatment Technologies For Amrsupporting
confidence: 92%
“…Diverse removal patterns were observed for the antibiotics, ARBs and ARGs during anaerobic digestion which is in complete agreement with previously reported studies (Youngquist et al, 2016). ARGs was achieved by cyclic activated sludge system (Wen et al, 2016).…”
Section: Treatment Technologies For Amrsupporting
confidence: 92%
“…changes of bacterial community composition was influenced significantly by environmental factors like pH, the properties of available nutrition, temperature and MC, these factors may affect the ARGs profiles through bacterial community indirectly. The operational condition may be the primary factor that governs the evolution of bacterial community and the subsequent prevalence of ARGs as suggested previously in anaerobic digestion (Youngquist et al, 2016). Considering controlling the ARGs, more researches should be done to improve these environmental factors through optimization of the key operational parameters, just like what has been done in this study that the improved aeration strategy in Pile I realized the higher reduction and less enrichment of ARGs.…”
Section: The Variation Of the Contributors To The Evolution Of Argsmentioning
confidence: 62%
“…Considering the huge amounts of swine manure, anaerobic digestion (AD) was widely adopted due to its effectiveness on the pathogens removal, volume reduction and resource utilization, especially the biogas production, and luckily, it was demonstrated that AD could also realize some ARGs reduction in swine manure (Youngquist et al, 2016). But the digestate still contributed a lot to the spread and proliferation of ARGs in the environment (Sui et al, 2016) and there was much space for the improvement of AD efficiency (Astals et al, 2012), which indicated that some work could be done to simultaneously enhance the AD efficiency and ARGs removal.…”
Section: Introductionmentioning
confidence: 99%